"I just forget to take it": asthma self-management needs and preferences in adolescents. (14th September 2015) - Koster, Ellen S.; Philbert, Daphne; de Vries, Tjalling W.; van Dijk, Liset; Bouvy, Marcel L.
Abstract: Background : Medication adherence rates often decline as children become teenagers. Effective adherence-enhancing interventions for adolescents are lacking. The objective of this study was to assess adolescent asthmatics needs and preferences regarding medication counseling and support, with focus on new media. Methods : Three focus groups including 21 asthmatic adolescents recruited from both primary and secondary care were held to explore needs and preferences regarding asthma-self management. Questions concerned adherence behavior and needs and preferences in adherence support with focus on new media (mobile technology, social media, health games). Results : Forgetting was mentioned as major reason for not using medication as prescribed. Adolescents also mentioned lack of perceived need or beneficial effects. Parents mainly play a role in reminding to take medication and collecting refills. The suggested strategies to support self-management included smartphone applications with a reminder function and easy access to online information. Participants were positive about sharing of experiences with other teenagers. Conclusion : Forgetfulness is a major reason for non-adherence in adolescents. Furthermore, our results suggest use of peer support may be helpful in promoting good medication use. Future interventions should be aimed at providing practical reminders and should be modifiable to individual preferences.